Batik Batik in the Joint Business Group of Sidomulyo, Tegal: A Case Study of the Ornamentation, Function, and Inheritance - Affan, Faiz; Triyanto, Triyanto; Iswidayati, Sri (Catharsis, 2019)
Producing art is a human need. This research focuses on the art production in the form of batik made by Sidomulyo Joint Business Group in Pasangan. This research aims to analyse the ornamentation of batik, explain the function of batik, and the inheritance to the next generation organized by the business group. This research employs qualitative method with socio-cultural interdiscipline and art. The researchers collected the data through observation, interview, and documentation. The analysis of the data focuses on the aesthetics, function, and the concept of inheritance (internalization, enculturation, and socialization). First, the business group produces batik with variative and aesthetics value. Second, the batik provides human value for the source of living, socialization, and cultural preservation. Third, the inheritance works through family’s intergenerational transfer and informal education. Batik Tegal has varied motives. The producer may preserve it by motivating the younger generation to keep on producing the batik in Tegal. As a suggestion, this research can become a reference for future generation about batik in Tegal and how to do it.